A ermida do Cristo do Silêncio - Miranda, B. P. (Architectures of the soul: Multidisciplinary approaches to the experiences and landscapes of seclusion and solitude, 2022)
The present text faces methodologically the research process that gained form and expression with the registration, in 2008, of a PhD thesis program, submitted to the Faculty of Architecture of the University of Porto, under the title: «Liturgy and architecture. Thinking a place for the liturgy: the aggiornamento as a program? » The circumstance of a theoretical reﬂection that developed at the same time of the project exercise would consolidate the need to articulate both processes. In a sense, one could say that the project gained – as a synthesis of a process of materialization of ideas, isolated in the research - the condition of object of study. The project of the «Christ of silence chapel» dealt with the same set of questions: how are architecture and liturgy inseparable and convergent in the project of a return to the originality of the Christian place? Moreover, how does this condition manifest itself in the process of the architectural project of a vacated space to welcome, all who seek recollection and the celebration of the liturgy?